2012
DOI: 10.1149/2.059301jes
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Morphologies of Fresh Produce on the Performance of Phage-Based Magnetoelastic Biosensors

Abstract: This study investigated the effects of different surface morphologies on the performance of phage-based magnetoelastic (ME) biosensors for Salmonella Typhimurium detection on selected fresh produce. The ME biosensor is composed of an ME resonator platform and filamentous E2 phage for the specific recognition of S. Typhimurium. After SEM observation of the surface morphologies of tomatoes and spinach (adaxial/abaxial), S. Typhimurium was inoculated serially onto the surfaces to examine the attachment and distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
0
14
2
Order By: Relevance
“…ME platforms were fabricated from METGLAS 2826MB alloy ribbon (Honeywell Inc., USA). The ribbon was diced into rectangular-shaped platforms with a size of 0.028 mm × 0.2 mm × 1 mm, using a computer controlled automatic micro-dicing saw (MPE Inc., USA) following the procedures mentioned in previous studies [17,18].…”
Section: Fabrication Of Magnetoelastic Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…ME platforms were fabricated from METGLAS 2826MB alloy ribbon (Honeywell Inc., USA). The ribbon was diced into rectangular-shaped platforms with a size of 0.028 mm × 0.2 mm × 1 mm, using a computer controlled automatic micro-dicing saw (MPE Inc., USA) following the procedures mentioned in previous studies [17,18].…”
Section: Fabrication Of Magnetoelastic Platformsmentioning
confidence: 99%
“…The binding of E2 phage and S. Typhimurium increases the total mass on the ME sensor, so the vibration of the ME sensor is decreased, resulting in a resonant frequency shift. The resonant frequency shift is directly proportional to the number of S. Typhimurium bound to the ME sensor; therefore, the target bacteria can be identified and quantified from the resonant frequency shifts of the ME sensor [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the LOD of the ME biosensor method was approximately 2 log lower than that of the SPR method using the same lytic phage (p < 0.05). In addition, previous studies [16,17,27,28] already demonstrated that the ME biosensor method was relatively fast (several minutes), cost effective (pennies/sensor), and simple in operation compared with other rapid detection methods such as real-time PCR and SPR. Since this study focused on the first application of a lytic phage on the ME biosensor method as a new bio-recognition element, the ME biosensors was applied to pure culture of MRSA instead of real food samples.…”
Section: Optimization Of the Concentration Of Bsamentioning
confidence: 99%
“…The ME biosensor method has been used successfully for the on-site detection of Salmonella and Bacillus anthracis spores [14][15][16][17]. However, to our knowledge, the ME biosensor method has so far not been used for MRSA detection.…”
Section: Introductionmentioning
confidence: 99%